Effects of media use, smart phone addiction, and adult ADHD symptoms on wellbeing of college students during the COVID-19 lockdown: Dispositional hope as a protective factor - Toma, Roxana Andreea; Anderson, Craig A.; Matichescu, Marius; Franţ, Anca; Almǎjan-Guţă, Bogdan; Cândea, Adela; Bailey, Kira (Frontiers in Psychology, 2022)
Introduction The present study investigated the role of dispositional hope as a potential protective factor moderator in the relationship between adult ADHD symptoms, media use/smart phone addiction and wellbeing during the period of isolation because of the COVID-19 pandemic among students in Romania. Methods A sample of 333 college students (86.8% female and 13.2% male) between the age of 18 and 47 with a mean of 20.6 years old from West University of Timişoara completed online surveys. Mediation and moderation analyses were performed to assess the associations among the variables. Results Results confirmed the negative associations of both adult ADHD and smartphone addiction with overall wellbeing. The smartphone addiction/ wellbeing association was moderated by dispositional hopefulness, such that high hopefulness served as a protective factor [b = −0.008, 95% percentile CI (−0.0134; −0.0012)]. Discussion Implications for the educational environment are discussed.